2017
DOI: 10.1002/jmri.25602
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vessel wall lesions and vascular stenoses on cerebrovascular reactivity in patients with intracranial stenotic disease

Abstract: Purpose To compare cerebrovascular reactivity (CVR) and CVR lagtimes in flow territories perfused by vessels with vs. without proximal arterial wall disease and/or stenosis, separately in patients with atherosclerotic and non-atherosclerotic (moyamoya) intracranial stenosis. Methods Atherosclerotic and moyamoya patients with >50% intracranial stenosis and <70% cervical stenosis underwent angiography, VWI, and CVR-weighted imaging (n=36; vessel segments evaluated=396). Angiography and VWI were evaluated for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…reaction time. As BOLD delay time assessment provides us with two important measures of cerebrovascular health, the technique has gained increasing attention ( Christen et al., 2015b ; Cogswell et al., 2017 ; Liu et al., 2017b ; Donahue et al., 2015 ; Champagne et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…reaction time. As BOLD delay time assessment provides us with two important measures of cerebrovascular health, the technique has gained increasing attention ( Christen et al., 2015b ; Cogswell et al., 2017 ; Liu et al., 2017b ; Donahue et al., 2015 ; Champagne et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some previous studies have tried to measure cerebrovascular reactivity using MRI and found that its impairment is involved in a variety of intracranial vascular pathogenesis, including both small and large vessel diseases. [31][32][33][34] These data indicate the importance of directly measuring local intracranial endothelial function. However, questions remain as to what extent these cerebrovascular reactivity measurements rely on intracranial endothelial cells since very few of these investigations had used direct endothelial-dependent stimuli (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…Vascular regulation and oxygen extraction at the microvascular level may also be impaired due to vessel wall damage that currently cannot be evaluated at the spatial resolution of human vessel wall sequences. Prior work in other populations has however shown that vessel wall disease is related to impaired cerebrovascular reactivity magnitude and timing, 11 which is logical in SCD as well and may be the topic of future studies. Vascular reactivity is well known to be largely mediated by autoregulation and relaxation of smooth muscle located within the middle tunica media layer of the arterial wall 37–40 .…”
Section: Discussionmentioning
confidence: 94%
“…hypercapnia) stimuli, 6–8 and these protocols have been successfully applied in individuals with SCD to elucidate reduced reserve capacity. Furthermore, in individuals with non‐atherosclerotic intracranial stenosis, cerebrovascular reactivity has been demonstrated to reduce with increasing intracranial arterial wall thickening, 11 yet whether arterial wall thickening is present in individuals with SCD has not been well studied.…”
Section: Introductionmentioning
confidence: 99%